PENINGKATKAN HASIL BELAJAR IPS PADA MATERI KEBUTUHAN MANUSIA MELALUI MODEL DISCOVERY LEARNING PADA SISWA KELAS VIIA DI SMPN 12 TANJUNG JABUNG TIMUR TA. 2021/2022 - Guswandi, Guswandi (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2022)
Based on the experience of researchers in class, on average, students in class VII experienced less motivation which had an effect on student learning outcomes. The teacher functions to generate student motivation by guiding students to be directly involved in active learning activities, especially in the Human Needs material. The Discovery Learning model is one of the learning models that directs these activities, the selection of the Discovery Learning learning model is a learning model that in addition to generating student motivation, also involves students in the search process for Human Needs material. The problems to be studied in this action research are: Can the use of the Discovery Learning model improve the learning outcomes of class VIIA students on Human Needs material at SMPN 12 Tanjung Jabung Timur in the 2021/2022 academic year? . Meanwhile, the objectives of this research are: To improve learning outcomes on the subject of Human Needs for class VIIA students at SMPN 12 Tanjung Jabung Timur in the 2021/2022 academic year. This study uses two cycles of action research. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this study was class VIIA students. The data obtained were in the form of formative test results, observation sheets for teaching and learning activities. From the results of the analysis, it was found that student learning achievement increased from cycle I to cycle II, namely, cycle I (55.56%) and cycle II (88.89%). The conclusion of this study is that learning the Discovery Learning model can have a positive effect on student learning outcomes VII A and this learning model can be used as an alternative to Social Science learning where students can explore and solve problems on the material.